2018
DOI: 10.3390/ijms19103055
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effective Biochar Produced from Agricultural Residues and Its Application for Preparation of High Performance Form-Stable Phase Change Material via Simple Method

Abstract: A new form-stable composite phase change material (PEG/ASB) composed of almond shell biochar (ASB) and polyethylene glycol (PEG) was produced via a simple and easy vacuum impregnation method. The supporting material ASB, which was cost effective, environmentally friendly, renewable and rich in appropriate pore structures, was produced from agricultural residues of almond shells by a simple pyrolysis method, and it was firstly used as the matrix of PEG. Different analysis techniques were applied to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 72 publications
(23 citation statements)
references
References 43 publications
(67 reference statements)
1
19
0
Order By: Relevance
“…The composite of PEG/MPC-Cu began to melt at 54.8 °C and to freeze at 38.4 °C, and the peak temperatures in the melting and freezing process were 60.1 °C and 33.5 °C, respectively. Compared to pristine PEG, the peak temperature values of the prepared ss-PCM were lower, which could be explained by the fact that adding MPC-Cu could increase the thermal conductivity of PEG 54 .
Figure 10 DSC curves for PEG, MPC-Cu and PEG/MPC-Cu.
…”
Section: Resultsmentioning
confidence: 94%
“…The composite of PEG/MPC-Cu began to melt at 54.8 °C and to freeze at 38.4 °C, and the peak temperatures in the melting and freezing process were 60.1 °C and 33.5 °C, respectively. Compared to pristine PEG, the peak temperature values of the prepared ss-PCM were lower, which could be explained by the fact that adding MPC-Cu could increase the thermal conductivity of PEG 54 .
Figure 10 DSC curves for PEG, MPC-Cu and PEG/MPC-Cu.
…”
Section: Resultsmentioning
confidence: 94%
“…This result indicated that, the formation of copper microspheres on the surface of WBB did not change the superficial chemical functional groups of WBB. In the spectra of WBB and CMS-WBB, the characteristic absorption peak at 1631 cm −1 originated from the tensile vibration of C=C group, while the peak at 1383 cm -1 was caused by C–C 16 , 26 , 27 . In addition, there were wide peaks at 1010–1120 cm −1 , which were typical graphite properties 18 , 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Among these carriers, biochar attracted much attention owing to its large specific surface and abundant functional groups, which was prepared by pyrolysing biomass, such as forestry and agricultural residues 15 . For example, Chen et al used almond shell biochar (ASB) as supporting material to load polyethylene glycol (PEG) for the synthesis of PEG/ASB ss-PCMs, and the experimental results showed that PEG/ASB had excellent thermal stability and phase transition properties 16 . Although the leakage problem of PCMs could be solved by using biochar as carrier, the thermal conductivity of ss-PCMs still needed to be further improved.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal conductivities of PA, PB and PA/PB-4 in this study were measured to be 0.2731, 0.3417 and 0.3926 W/(m∙K), respectively. The conductivity of PB was not very high, and however, it could improve the PA’s conductivity effectively for the reason that when PA was filled into the pores of PB, it could replace the air in the pores, and then the conductivity of PA/PB would be improved and higher than that of both PA and PB 42 . Additionally, the thermal conductivities of different form-stable phase change materials are listed in the Table 4.…”
Section: Resultsmentioning
confidence: 99%